2021
DOI: 10.3390/pharmaceutics13081190
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Properties of Modified Pharmaceutical Bentonite with Zinc and Copper

Abstract: Pharmaceutical grade bentonite, containing a high amount of montmorillonite, enriched with zinc (Zn) or copper (Cu) (ZnBent and CuBent, respectively) was used as the main component for the creation of formulations for cutaneous use and tested for their antimicrobial capacity. Bentonite (Bent) with added phenoxyethanol (PH) as a preservative and unmodified bentonite were used as control groups. The mineralogical composition, structural state, and physical or chemical properties, before and after the modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…18 Besides AgMMT, the antibacterial activities of ZnMMT and CuMMT have also been studied. [19][20][21] All these studies have implied that MMT has a promising application in the antibacterial field. However, most of these ion-exchanged antibacterial MMT do not show good cytocompatibility, 19,22 which limits their application in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…18 Besides AgMMT, the antibacterial activities of ZnMMT and CuMMT have also been studied. [19][20][21] All these studies have implied that MMT has a promising application in the antibacterial field. However, most of these ion-exchanged antibacterial MMT do not show good cytocompatibility, 19,22 which limits their application in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Bentonite is a natural safe clay material, abundant in Jordan with low cost, and convenient for use in animal feed. The antibacterial properties of bentonite have been confirmed (Martsouka et al, 2021). Due to their healing and antimicrobial properties, bentonites are widely used 142 in the pharma, cosmetics, and agriculture industries (Srasra et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have demonstrated that due to its outstanding physico-chemical properties, including small grain size (in the micrometric order), and large specific surface area (of approximately 100 m 2 /g), ensuring high adsorption, swelling, intercalation, and cation-exchange capacity, mineral clays can be used as carrier materials or drug-delivery-system substrates or supports [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various studies have confirmed the biological properties of clay minerals and reported high chemical stability and the absence of toxicity in vivo. Currently, clay mineral applications are used as active agents or excipients in numerous pharmaceutical and dermato-cosmetic preparations [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%